Patrones De Disciplina Basados En El Maltrato Familiar Y Su Repercusión En La Formación De Valores Morales En La Escuela De Educación Básica “Amazonas”, Del Recinto Amazonas, Parroquia Camilo Ponce, Cantón Babahoyo, Provincia Los Rios. - Vaca Quijije, Raquel (2014)
This study aimed to determine patterns of discipline based on family abuse that affect the formation of moral values in students of the School of Basic Education "Amazonas Amazonas Campus, Camilo Ponce Parish, Canton Babahoyo Province Los Ríos. The research methodology was descriptive, bibliographic, and electronic field, applying the survey as instruments led to a population sample of 3 teachers, 53 students and 48 parents, concluding that the most common form of abuse is psychological abuse and authoritarianism prevailing attitude in parents, and sometimes overprotective, which is affecting the crisis of values of students in the school context, thereby generating the indiscipline in the classroom. Therefore arises as proposed developing a School for Parents program intervention strategies that optimize the moral values and improve family life, classroom and community. This work aims to meet the expectations research and contribute to improving the quality of life for educating optimizing their family context.